2016
DOI: 10.11648/j.jfns.20160405.12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Lipid Assessment and Arterial Lesions Observed in Farm Chickens Fed on Different Vegetable Oils

Abstract: The objective of this study was to determine the relationship between lipid assessment (total-cholesterol, HDLcholesterol, LDL-cholesterol, triacylglycerols) and arterial lesions in farm chickens fed on six different vegetable oil varieties (crude red palm oil, industrial red palm oil, refined palm oil, soya oil, cotton oil, and groundnut oil). The following emerged from the different analyses: palm oil, and, to a lesser extent, soya oil and cotton oil, tended to lower the total cholesterol rate whereas ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Thus, Voon et al (2011) found a non-significant difference (p> 0.05) between the impact of palm oil consumption and olive oil consumption on serum concentrations of LDL cholesterol (Voon, Ng, Lee, & Nesaretnam, 2011). In Côte d'Ivoire, we studied changes in lipid profile in farm chickens fed with different varieties of vegetable oils, including palm oil which had a cholesterol-lowering effect (Mondé et al, 2016). This study also indicated that consumption of this oil decreased serum levels of triglycerides and LDL cholesterol but increased HDL cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Voon et al (2011) found a non-significant difference (p> 0.05) between the impact of palm oil consumption and olive oil consumption on serum concentrations of LDL cholesterol (Voon, Ng, Lee, & Nesaretnam, 2011). In Côte d'Ivoire, we studied changes in lipid profile in farm chickens fed with different varieties of vegetable oils, including palm oil which had a cholesterol-lowering effect (Mondé et al, 2016). This study also indicated that consumption of this oil decreased serum levels of triglycerides and LDL cholesterol but increased HDL cholesterol.…”
Section: Introductionmentioning
confidence: 99%